2013
DOI: 10.1080/01443410.2013.797338
|View full text |Cite
|
Sign up to set email alerts
|

Taking working memory training from the laboratory into schools

Abstract: Working memory skills have been shown to be enhanced by adaptive training in several randomised controlled trials. Here, two field trials were conducted in which teachers administered working memory training to their own pupils in school. Twenty-two children aged 8–9 years participated in Trial 1. In Trial 2, 50 children aged 9–11 years with the lowest academic performance completed training. They were matched with a group of 50 children who were not trained. Following training, children in Trial 1 improved si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
143
0
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(182 citation statements)
references
References 35 publications
12
143
0
15
Order By: Relevance
“…Next, in the first of several explorations of far-transfer effects, we found that ACT resulted in significant improvements in verbal WM compared to the untrained group, with a more moderate effect size (d = .75), identical to the effect size reported by Holmes and her colleagues in their recent study with older children for transfer to verbal WM (Holmes & Gathercole, 2013). This finding adds to the literature that WM may involve some domain-general aspects, possibly involving controlled attention or executive attention mechanisms (Chein, Moore, & Conway, 2011).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Next, in the first of several explorations of far-transfer effects, we found that ACT resulted in significant improvements in verbal WM compared to the untrained group, with a more moderate effect size (d = .75), identical to the effect size reported by Holmes and her colleagues in their recent study with older children for transfer to verbal WM (Holmes & Gathercole, 2013). This finding adds to the literature that WM may involve some domain-general aspects, possibly involving controlled attention or executive attention mechanisms (Chein, Moore, & Conway, 2011).…”
Section: Discussionsupporting
confidence: 61%
“…It is vital in studies of ACT that near-transfer be established before any possible far-transfer effects can be interpreted (Melby-Lerväg & Hulme, 2013). We found that ACT substantially improved visuospatial WM in untrained tasks and the effect size was very large (d = 1.44), comparable to the effect size for transfer to untrained visuospatial tasks in a prior study (effect size = .95) with older children (Holmes & Gathercole, 2013).…”
Section: Discussionsupporting
confidence: 59%
“…Several longitudinal studies have confirmed that working memory explains a significant part of the variance in mathematics (see Raghubar et al, 2010, for an overview). Even a causal role has been suggested by experimental studies in which children's working memory skills were manipulated (e.g., Bergman-Nutley & Klingberg, 2014;Holmes & Gathercole, 2014;Kroesbergen, Van 't Noordende, & Kolkman, 2014;Söderqvist & Bergman-Nutley, 2015), although the meta-analysis of Melby-Lervåg and Hulme (2013) shows that there is no clear evidence of generalization of working memory training to math skills. It should be noted that in the literature working memory sometimes refers to the entire processing and storage unit as described by Baddeley and Hitch (1974), while other use it to refer only to the central executive, or even more specifically to the executive function of updating (see also Friso-Van den Bos et al, 2013).…”
Section: Working Memorymentioning
confidence: 99%
“…This means that educators have to start with identification of learners with poor WM, decide which components are problematic, and apply proper, individualized training. There is a large body of empirical evidence showing that deficits in both the phonological store and attentional system severely impair language learning (Gathercole, Lamont, & Alloway, 2006), and that these deficits can be leveled out to some extent thanks to adept pedagogic intervention (Gathercole 2014;Gathercole & Alloway, 2008;Holmes & Gathercole, 2014;Söderqvist & Nutley, 2015). Gathercole and colleagues have provided evidence that skillful training in the case of young children whose general academic performance is severely affected by poor WM produces considerable and sustained results.…”
Section: Working Memorymentioning
confidence: 99%